How does heterogeneous green technology innovation affect air quality and economic development in Chinese cities? Spatial and nonlinear perspective analysis - Zhongqingyang Zhang; Zhongbao Zhou; Zhijian Zeng; Yuxuan Zou (Journal of Innovation & Knowledge, 2023)
This study considers spatial and nonlinear perspectives to examine the heterogeneous role of green technology innovation in the economic development and air quality of Chinese cities. We find that green inventive technology innovation benefits economic development and air quality improvement, which have significant spatial spillover effects. Conversely, green improved technology innovation has no significant spatial spillover effect on air quality. The results show that urban heterogeneity exists in the effects of green technology innovation on the economy and air quality. From a regional perspective, green technology innovation in the central region improves air quality in neighboring cities; however, no effective spatial synergy mechanism has been established within other regions. From an administrative perspective, green technology innovation in municipalities and provincial capitals can effectively drive the win–win development of the urban economy and environment. Moreover, this study verifies the nonlinear effect of economic development; the single-threshold result indicates that an increase in the level of regional economic development facilitates the effect of green technology innovation to improve air quality. Furthermore, we elucidate the mediating role of economic development. This findings of this study offer decision-making guidance to drive economic and environmental win–win development through green technology innovation and achieve synergistic regional green development.